Sistem Stok Barang Berbasis Rfm Dengan Mempertimbangkan Kebiasaan Konsumen Dan Barang Slow-Moving Di Usaha Konter - Wijayanti, Lusi Salsabilla; Bianto, Mufti Ari; Zamani, Sevian Nadi; A, Dwi Putra (Innovative: Journal Of Social Science Research, 2025)
Mobile phone accessory stores, particularly those selling accessories and spare parts, face challenges in managing stock accumulation, especially with slow-moving items that are rarely purchased. This study aims to implement the RFM (Recency, Frequency, Monetary) method to segment customers based on their transaction behavior and relate it to product movement. Through this analysis, store owners can identify which products are fast-moving or slow-moving, and which customers actively contribute to inventory turnover. The segmentation results support better decision-making in promotional strategies, restocking the right products, and managing discounts for rarely sold items. This research shows that the RFM approach is not only useful for customer management, but also effective in enabling a more adaptive and efficient inventory management system.